Oil: Rich Man Poor Man - "Khera, S. S." (New Delhi, 1979)
Bureaucrats write books as if they were dictating background notes for their ministers and naturally draw heavily on other official notes and reports. No wonder, such books make dull reading. But Khera's book, serves one good purpose it provides convenient summaries of reports by umpteen study groups and inquiry committees that have gone into India's oil problem
Keywords: Petrolium industry .